On Stability of a Unit Ball in Minkowski Space with Respect to Self-Area - Shcherba, A.I. (Журнал математической физики, анализа, геометрии, 2011)
The author expresses his sincere gratitude to V.I. Diskant for his useful discussions of the considered problem.